Treatment induced clearance of hepatitis E viruses by interferon‐lambda in liver‐humanized mice. (29th August 2021) - Sari, Gulce; Mulders, Claudia E.; Zhu, Jingting; van Oord, Gertine W.; Feng, Zongdi; Kreeft‐Voermans, Jolanda J.C.; Boonstra, Andre; Vanwolleghem, Thomas
Abstract: Background: Hepatitis E viruses (HEV) are an underestimated global cause of enterically transmitted viral hepatitis, which may persist in immunocompromised hosts, posing a risk for progressive liver fibrosis with limited treatment options. We previously established liver‐humanized mice as a model for chronic HEV infections, which can be cleared by a 2‐week pegylated (peg)‐Interferon(IFN)α treatment course. However, severe side effects may hamper the use of IFNα in immunocompromised transplant recipient patients. IFNλ may be a valuable alternative, as its receptor is less ubiquitously expressed. Aims: In this study, we assess the in vitro and in vivo potency of pegIFNλ to induce innate immune signalling in liver cells and to clear a persistent HEV infection in liver‐humanized mice. Methods & Results: We found that human liver cells expressed the IFNλ receptor (IFNLR1) and are responsive to pegIFNλ. Treatment with pegIFNλ of liver‐humanized mice persistently infected with HEV genotype 3 showed that pegIFNλ was well tolerated. Dose escalation studies showed that although HEV was not cleared at pegIFNλ doses up to 0.12 mg/kg for a maximum of 8 weeks, a dose of 0.3 mg/kg pegIFNλ treatment resulted in complete clearance of HEV antigen and HEV RNA from the liver in 8 out of 9 liver‐humanized mice. Conclusions: PegIFNλ is well tolerated in mice and leads to clearance of a persistent HEV infection in liver‐humanized mice.